Experimental Approach to Flint Shaft Mining: Understanding the Extraction Process and the Technical Gesture at Casa Montero (Madrid, Spain) - Marie-Élise Porqueddu; Nuria Castañeda Clemente; Javier Baena Preysler (EXARC Journal)
Since prehistory, human populations have developed specific knowledge related to the excavating and exploitation of underground resources. These abilities are reflected in the tools used to extract and process raw materials and the use of specific architectural expressions such as rock-cut tombs. As part of these practices, Neolithic human groups used a range of techniques that were closely connected to the environmental constraints of the subterranean sphere. As part of a study of both mining and burial structures in the Madrid region during the Neolithic period, we are investigating the technical gestures used in extracting flint from shafts by means of experimentation. The case study we have chosen is the Casa Montero mining site. With more than 4,000 extraction pits over a period of use of several hundred years, Casa Montero is one of the oldest flint extraction sites on the Iberian Peninsula. This study, therefore, focuses on the excavation of an experimental flint extraction pit like the structures found at Casa Montero.